ANALISIS FRAMING TERKAIT PEMBERITAAN JOKOWI YANG MENYERANG PRIBADI PRABOWO PADA DEBAT CALON PRESIDEN PUTARAN KEDUA TAHUN 2019 DALAM “mediaindonesia.com” - Stepanus Sitanggang; Dina Fadiyah (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2020)
This paper will discuss Analysis of Framing Related to the Coverage of Jokowi Who Attacked Prabowo in the Second Round of Presidential Candidates for 2019 in "mediaindonesia.com". The purposes of this paper are (1) To find out a picture of how media framing mediaindonesia.com in delivering an incident related to Jokowi who personally attacked Prabowo in the second round of Presidential candidates in 2019. (2) To find out the relationship between mediaindonesia.com and democracy in reporting of Jokowi who personally attacked Prabowo at the second round of the Presidential debate in 2019. The research used the Theory of Framing Analysis from Gamson and Modigliani. This research method used qualitative research. The results of this research explain that (1) Framing of mediaindonesia.com reporting in presenting an incident related to Jokowi who personally attacked Prabowo in the second round of Presidential candidates in 2019. (2) There was a connection between mediaindonesia.com and democracy in reporting of Jokowi on personality of Prabowo in debating the second round of the Presidential candidates in 2019. So, the conclusion of this research shows that in mediaindonesia.com reporting, it emphasizes what supports Jokowi and shows the point of view that leads to the control of the land owned by Prabowo. Mediaindonesia.com's partisanship supports the diminishing democratic values in Indonesia where the media are the fourth pillar of democracy itself.